DETERMINATION OF THE LEVEL OF RISKS IN INVESTMENT PROJECTS USING ECONOMETRIC MODEL - BUSTONOV MANSURJON MARDONAKULOVICH; RAKHIMOV BAHROMJON IBROXIMOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
Particular study of the effective use of investments, including foreign investments, on technical andtechnological modernization of enterprises and diversification of products in the conditions of modernizationof the economy, ensuring the competitiveness of manufactured products and services in the world market isone of the most important tasks of today.Today, further reforming and liberalizing the Uzbek economy should accelerate the improvement of theinvestment climate in the industrial sector, especially with the development of the private sector.